KAJIAN KAPASITAS RUMAH TANGGA TERHADAP BENCANA KABUT ASAP DI KELURAHAN BANSIR DARAT, KOTA PONTIANAK - Aji Rio Sutrisno; Djoko Santoso Abi Suroso (Diponegoro University, 2018)
Forest and land fires (karhutla) in Indonesia cause environmental degradation, economic losses and health problems. The phenomenon of Strong El Nino becomes a natural factor that exacerbates the condition of karhutla, efforts to reduce the risk of karhutla by preventing, reducing and tackling the karhutla continue to be pursued by the government. The haze of karhutla becomes a problem in itself, the extent of exposed areas and dangerous particles disrupt the activities of the community, especially health problems. Disaster risk reduction efforts can be done by increasing capacity, while one type of capacity in the community is household capacity. The purpose of this study is to review the capacity of households in the face of smoke haze karhutla, the location chosen to conduct the study is Kelurahan Bansir Darat, Pontianak City-West Kalimantan. The discussion begins with determining the criteria of household capacity, the data sampling technique is non probability sampling in the form of systematic sampling through questionnaire amounting to 110 and the method of data analysis is done quantitatively descriptive and quantitative associations. Identified household characteristics were age group, occupation group and settlement type, household capacity calculation showed that 21.82% were ready, 28.18% were not ready and 50.00% were adequately prepared for the disaster, found significant relationship between work groups with household capacity and type of settlement with household capacity.